A Folate Receptor-Targeting Nanoparticle Minimizes Drug Resistance in a Human Cancer Model - Wang, Xu (2011)
Resistance to chemotherapy is a major obstacle in cancer therapy. The main purpose of this study is to evaluate the potential of a folate receptor-targeting nanoparticle to overcome/minimize drug resistance and to explore the underlying mechanisms. This is accomplished with enhanced cellular accumulation and retention of paclitaxel (one of the most effective anticancer drugs in use today and a well-known P-glycoprotein (P-gp) substrate) in a P-gp-overexpressing cancer model. The folate receptor-targeted nanoparticle, HFT-T, consists of a heparin-folate-paclitaxel (HFT) backbone with an additional paclitaxel (T) loaded in its hydrophobic core. In vitro analyses demonstrated that the HFT-T nanoparticle was superior to free paclitaxel or non-targeted nanoparticle (HT-T) in inhibiting proliferation of P-gp-overexpressing cancer cells (KB-8-5), partially due to its enhanced uptake and prolonged intracellular retention. In a subcutaneous KB-8-5 xenograft model, HFT-T administration enhanced the specific delivery of paclitaxel into tumor tissues and remarkably prolonged retention within tumor tissues. Importantly, HFT-T treatment markedly retarded tumor growth in a xenograft model of resistant human squamous cancer. Immunohistochemical analysis further indicated that increased in vivo efficacy of HFT-T nanoparticles was associated with a higher degree of microtubule stabilization, mitotic arrest, antiangiogenic activity, and inhibition of cell proliferation. These findings suggest that when the paclitaxel delivered as an HFT-T nanoparticle, the drug is better retained within the P-gp-overexpressing cells than the free form of paclitaxel. These results indicated that the targeted HFT-T nanoparticle may be promising in minimizing P-gp related drug resistance and enhancing therapeutic efficacy compared with the free form of paclitaxel.